Emotion and affect in mental imagery: do fear and anxiety manipulate mental rotation performance? - Kaltner, Sandra; Jansen, Petra (Frontiers in Psychology, 2014)
Little is known about the effects of fear as a basic emotion on mental rotation (MR) performance. We expected that the emotional arousal evoked by fearful stimuli presented prior to each MR trial would enhance MR performance. Regarding the influence of anxiety, high anxious participants are supposed to show slower responses and higher error rates in this specific visuo-spatial ability. Furthermore, with respect to the embodied cognition viewpoint we wanted to investigate if the influence of fear on MR performance is the same for egocentric and object-based transformations. To investigate this, we presented either negative or neutral images prior to each MR trial. Participants were allocated to the specific emotion in a randomized order. Results show that fear enhances MR performance, expressed by a higher MR speed. Interestingly, this influence is dependent on the type of transformation: it is restricted to egocentric rotations. Both observation of emotional stimuli and egocentric strategies are associated with left hemisphere activation which could explain a stronger influence on this type of transformation during observation. Another possible notion is the conceptual link between visuo-spatial perspective taking and empathy based on the co-activation of parietal areas. Stronger responses in egocentric transformations could result from this specific link. Regarding the influence of anxiety, participants with high scores on the trait-anxiety scale showed poor results in both reaction time and MR speed. Findings of impoverished recruitment of prefrontal attentional control in patients with high scores in trait anxiety could be the explanation for this reduced performance.